Redações midiatizadas: etnografia das práticas jornalísticas no Brasil e na Suécia a partir de relações simbióticas - Marcellino, Marcio Morrison Kaviski (Universidade do Vale do Rio dos Sinos, 2024)
This thesis emerges from the question: how do symbiotic relationships, part of the context of mediatization, modify journalistic practices in newsrooms in Brazil and Sweden? What practices are changed in each context? With this, it aims to understand how symbiotic relationships, characteristic of a mediatization scenario, reshape journalistic practices and newsrooms in Brazil and Sweden. Furthermore, the following specific objectives are: a) Understanding how the process of circulation of meanings is present in the structuring and production of journalistic content through symbiotic relationships in both contexts b) Identifying how the environment has modified practices of news construction in Brazil and Sweden c) Measure how the pandemic affected journalistic practices; news products and newsrooms in Brazil and Sweden d) Observe consumption based on the circulation of meanings of social actors in both contexts e) Propose the concept of mediatized newsrooms. In the theoretical field, the thesis highlights the discussion about symbiotic relationships in Communication with authors such as Marcellino and Fort; Joel de Rosnay, Daniel Miller, Stina Begntsson, among others. In a second moment, theories of mediatization, mediatized journalism and journalistic practices are discussed with the contribution of theorists such as Ana Paula da Rosa, José Luiz Braga, Pedro Gilberto Gomes, Antônio Fausto Neto, etc. In a third theoretical moment, the thesis seeks to discuss the concept of device on two fronts: interactional and technical. To do this, we sought support in discussions by José Luiz Braga, Giorgio Agamben, Villém Flusser, Giorgio Simondon, among others. As a way of answering the current question in the thesis, the methodological constitution of this work was based on ethnography. In Sweden, seven journalists from different newsrooms (Dagens ETC, T&T News Agency, Sverige Radio and a Freelancer) were interviewed. In Brazil, the ethnographic process was outlined based on a two-week participant observation in the Curitiba newspaper Paraná Portal. In addition, three interviews were carried out with professionals who work in this newsroom. This thesis highlights the concept of mediatized newsrooms, journalism newsrooms that function in a deterritorial or hybrid manner, with workspaces that are extended through technological devices and applications affecting production, reception and distribution logics.
Keywords: Redações midiatizadas; Relações simbióticas; Jornalismo midiatizado; Midiatização; Ambiência; Mediatized newsrooms; Symbiotic relationships; Mediatized journalism; Mediatization; Ambience; ACCNPQ::Ciências Sociais Aplicadas::Comunicação